Achieving a large field-induced polarization and energy density in BaTiO3 films sputter-deposited on Si at 200 °C via a buffer-layer technique - Chao Liu; Jun Ouyang; Yuyao Zhao; Hanfei Zhu; Hongbu Cheng; Zhenyan Liang; Li Wang (Journal of Advanced Ceramics)
Ferroelectric oxide films with a large field-induced polarization can be used in dielectric capacitors for charge or energy storage in microelectronic systems and hence have attracted intense research interest. A high processing temperature is usually required to produce a well-crystallized polar phase and hence a large polarization in the film, corresponding to a high charge or energy density. However, high processing temperature not only reduces the charge‒discharge efficiency by producing a sizable remnant polarization but is also incompatible with the integration process. In this study, we address this problem by creating a large field-induced polarization (~55.8 μC/cm2) in BaTiO3 films sputter-deposited on Si at 200 °C via a buffer-layer technique. This large polarization led to a high energy density and efficiency (Wrec ≈ 94.7 J/cm3, η ≈ 78.2%@4 MV/cm). The thickness of LaNiO3 buffer layer was revealed to be the key factor determining the electric polarization (remnant and field-induced ones). A 50 nm LaNiO3 thickness, corresponding to the aforementioned polarization and energy storage performance, not only ensures proper crystallization in the BaTiO3 film, but also leads to an optimal combination of polycrystalline grains with a high dielectric constant. The latter accounts for the majority of the field-induced polarization. Our results revealed the key role of a buffer layer in tuning the microstructure of a low-temperature deposited ferroelectric oxide film. Furthermore, the excellent charge/energy storage performance of these 200 °C-deposited BaTiO3 films has provided many opportunities for this simple dielectric in microelectronics.